Pendampingan Penulisan Cerpen untuk Membangkitkan Imajinasi dan Keahlian Komunikasi Verbal Pelajar di SMPN 3 Meurebo - Zuhri, Al; Fadilah, Misnatul Nur; Alfizra, Luthfi; Nur, Marfirah; Nuriati, Rahma; Rahmalia, Rahmalia; Leni, Mahza; Refita, Refita; M, Deddy Satria; Nurdin, Ibnu Phonnna; Khairina, Ulfa (Universitas Teuku Umar, 2024)
This community service program aims to improve students’ writing literacy and verbal communication skills through short story writing mentorship at SMPN 3 Meurebo. The initiative was motivated by the low level of interest and creative writing ability among students, which limits their capacity to express ideas and imagination in written form. Activities were conducted face-to-face using a participatory approach and the fun learning method to create enjoyable, collaborative, and reflective learning experiences. The program was implemented in three stages: preparation, mentoring, and evaluation. Evaluation was carried out using pre-test and post-test assessments to measure participants’ progress. The results showed a significant improvement in students’ writing competence, with the average score increasing from 41% to 83%. The most notable improvement occurred in the understanding of intrinsic and extrinsic story elements, demonstrating the effectiveness of the mentoring model in strengthening conceptual comprehension and practical writing skills. The program also had a positive impact on students’ motivation, self-confidence, and creativity in writing. Overall, this activity successfully fostered literacy enthusiasm and supported the development of a creative learning ecosystem. The outcomes are expected to serve as a replicable model for writing literacy programs in other schools, particularly in regions with similar challenges in promoting a literacy culture.